Modelos preditivos para equilíbrio de fases de misturas hidroalcoólicas multicomponentes presentes na concentração e desidratação de etanol de 1ª e 2ª geração - Matugi, Karina (2017)
The production increase of the ethanol from sugarcane, ensuring energy and environmental viability, goes through the development of the step with highest energy consumption: the separation process in the distillation columns. The separation is an outcome from the volatility difference among the mixture components in a supposed VLE (vapor-liquid equilibrium). This work investigated the VLE phenomenon of three case studies: the ethanol concentration from a multicomponent mixture of wine; the removal of furfural and hydroxymethylfurfural from a hydroalcoholic solution from the production of second generation ethanol; and the dehydration of hydrous ethanol using glycerol and a salt (calcium chloride or potassium acetate). The “gamma-phi” equation was analyzed emphasizing the determination of the activity coefficient by predictive models based on group contribution. The F-SAC model (Functional – Segment Activity Coefficient) revealed promising among the models and with fewer parameters than the other ones. For all tested models, the VLE simulations for the isomers 2-methyl-1-butanol and 3-methyl-1-butanol, and for monoethylene glycol and glycerol resulted in significant deviations. Besides, VLE data for systems containing furfural and hydroxymethylfurfural and glycerol with a salt were obtained. The parameter of the UNIDMD and F-SAC models were reassessed using the assembled literature data, and new parameters are estimated for new components without functional groups predefined by the model.